A literature review of spiritual psychotherapy using Quran recitation in the treatment of drug addiction - Mohd Zohdi Mohd Amin; Abdulloh Salaeh; Mahsor Yahya; Zamrie Ibrahim @ Musa; Adnan Mohamed Yusoff; Norhasnira Ibrahim; Syed Najihuddin Syed Hassan; Robiatul Adawiyah Mohd @ Amat; Tazul Islam; Abas, Siti; Arifin, Mohd Syakir (American Scientific Publishers, 2024)
Indexed by Scopus